2011
DOI: 10.1097/cnq.0b013e3182048022
|View full text |Cite
|
Sign up to set email alerts
|

Legionella—Every Infection Preventionist's Dream—Or Is It?

Abstract: Legionella is an underreported disease challenge within the hospital setting. In order to combat Legionella during times of construction and renovation, infection preventionists must become construction experts. The infection preventionist must be able to plan for potential waterborne disease outbreaks and protect the hospital staff, patients and visitors from waterborne pathogens. Legionella's history, signs and symptoms, diagnostic testing and treatment will be discussed. The hospital's convening of a multid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The present study found 697 (78%) disease cases and 83 (74%) deaths were associated with Legionella, spp. [16,[18][19][20][21][22][23]25,26,[29][30][31][32][35][36][37][38][39][40][41][42][43][44][45][46]. Other opportunistic waterborne pathogens such as NTM and Sphingomonas, spp.…”
Section: Gap #4: Moving Beyond Legionellamentioning
confidence: 99%
“…The present study found 697 (78%) disease cases and 83 (74%) deaths were associated with Legionella, spp. [16,[18][19][20][21][22][23]25,26,[29][30][31][32][35][36][37][38][39][40][41][42][43][44][45][46]. Other opportunistic waterborne pathogens such as NTM and Sphingomonas, spp.…”
Section: Gap #4: Moving Beyond Legionellamentioning
confidence: 99%
“…Legionella creates biofilm within plumbing fixtures, hot water systems, HVAC cooling towers, condensers, humidifiers, fountains, shower heads, storage tanks and stagnant water. Legionella has been under reported; the fatality rate of Legionella pneumonia of hospital patients is as high as 40% [19] Testing piping following utility disruptions; before and after construction will identify risk and lines can be flushed and/or treated to prevent transmission to consumers. Care must be taken not only in areas of active construction but also in areas that have been closed during construction, and areas that share mechanical systems, domestic water systems, portable water and sanitary sewers.…”
Section: Hospital Acquired Infectionsmentioning
confidence: 99%